Corn Marketing Value Chain Analysis In Kedamean District, Gresik Regency - administrator, administrator; Udin, Imamul Bahak; Susanto, Heri; Dianto, Andri Krisna (Fakultas Pertanian Universitas Wijaya Putra, 2022)
This examine targets to identify the development of corn manufacturing, examine mapping, market cost chain evaluation of corn and broaden techniques for strengthening corn production in Kedamean District, Gresik Regency. The kinds and assets of records used in this study used kinds of records, particularly number one statistics and secondary records. The method of collecting statistics is purposive sampling, that is meant to make it less difficult for researchers to get facts related to analyze goals. The data evaluation used is cost chain evaluation. The results of this have a look at have been (1) manufacturing of composite maize via farmers in Kedamean District become able to attain production of 5-6 heaps per ha, whilst hybrid corn became capable of attain eight-10 lots in line with ha. The maize price chain in Kedamean District entails three (three) main actors, particularly: (1) Farmers (2) creditors (three) traders. the advertising chain above shows that the most important brought price is obtained via collectors and buyers. The advertising channels are marketing Channel I: Farmers – conventional markets – consumers, marketing Channel II: Farmers – provincial buyers – nearby/export clients, advertising Channel III: Farmers – district investors – provincial investors – local/export clients. advertising Channel IV: Farmers – collectors – district traders – provincial buyers – nearby/export purchasers.Keywords: corn, marketing value chain, marketing channel.